2015
DOI: 10.1007/s10585-015-9724-3
|View full text |Cite
|
Sign up to set email alerts
|

MiR-9 and miR-21 as prognostic biomarkers for recurrence in papillary thyroid cancer

Abstract: Despite low mortality rates, nodal recurrence in papillary thyroid carcinoma occurs in up to 20 % of patients. Emerging evidences indicate that dysregulated microRNAs are implicated in the process of metastasis. In the present study, we investigated whether miR-9, miR-10b, miR-21 and miR-146b levels are predictive of papillary thyroid carcinoma recurrence. Using macro-dissection followed by quantitative real-time PCR, we measured miR-9, miR-10b, miR-21 and miR-146b expression levels in formalin-fixed, paraffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 81 publications
(104 reference statements)
8
78
0
2
Order By: Relevance
“…In TCGA data, a more aggressive phenotype of thyroid cancer was also correlated with overexpression of miR-21 and miR-146b, as well as the loss of miR-204 (47). Later, the expression levels of miR-21 and miR-9 were also associated with the metastatic potential of tumor cells and proved to be good predictors of nodal metastasis (53).…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…In TCGA data, a more aggressive phenotype of thyroid cancer was also correlated with overexpression of miR-21 and miR-146b, as well as the loss of miR-204 (47). Later, the expression levels of miR-21 and miR-9 were also associated with the metastatic potential of tumor cells and proved to be good predictors of nodal metastasis (53).…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…However, only sporadic studies have so far focused on the association between miR deregulation and thyroid cancer prognosis and therapy [40,55,56,57,58,59]. …”
Section: Prognostic Mirsmentioning
confidence: 99%
“…Therapeutic inhibition of miR-146b in dedifferentiated thyroid carcinoma represents a promising way to enhance radioiodine uptake and the efficacy of radioactive therapy [57]. However, Sondermann et al [59] found no significant differences in miR-146b expression between recurrent and nonrecurrent papillary carcinomas.…”
Section: Prognostic Mirsmentioning
confidence: 99%
“…Thyroid cancer is the most common subtype of endocrine malignancy, with 300,000 new cases per year, and ~40,000 mortalities per year, worldwide (1). The incidence of thyroid cancer has increased in recent decades (2).…”
Section: Introductionmentioning
confidence: 99%